Origins : how the nine months before birth shape the rest of our lives - Paul, Annie Murphy (New York : Free Press, 2010)
What makes us the way we are? Is it the genes? The childhood environment? Or could it be that many of our individual characteristics--our health, our intelligence, our temperaments--are influenced by conditions encountered before birth? That's the claim of a provocative field known as fetal origins. Scientists are developing a radically new understanding of our very earliest experiences and how they exert lasting effects on us well into adulthood. Their research offers a bold new view of pregnancy as a crucial staging ground for our health, ability, and well-being throughout life. Journalist Annie Murphy Paul ventures into the laboratories, interviews experts from around the world, and delves into the rich history of ideas about how we're shaped before birth. The fetus is not an inert being, but an active and dynamic creature--and the pregnant woman is a source of influence on her future child far more powerful and positive than we ever knew.--From publisher description.
One month -- Two months -- Three months -- Four months -- Five months -- Six months -- Seven months -- Eight months -- Nine months.
Includes bibliographical references (p. 241-285) and index.
Keywords: Pregnancy -- Psychological aspects -- Popular works; Fetus -- Development -- Popular works; Prenatal diagnosis -- Popular works; Pregnancy; Embryonic and Fetal Development; Maternal-Fetal Relations; Pregnancy -- Psychological aspects; Fetus; Prenatal diagnosis